Pengaruh Edukasi Praktik Cuci Tangan Pakai Sabun terhadap Peningkatan Pengetahuan Anak di Masa Pandemi - Evy Tri Pratiwi; Devi Safira Damayanti; Galuh Sekar Anggraeni; Melinia Dwi Tanti; Tatut Isna Winanda; Vidia Nuria Rahman; Ayik Mirayanti Mandagi; Septa Indra Puspikawati (Universitas Negeri Malang, 2022)
The Ministry of Health swiftly carried out control efforts by releasing Circular No. HK.02.02/I/385 to simultaneously actively participate in preventing the transmission of COVID-19 through the Masks for All movement and the provision of hand washing facilities with soap (CTPS). The purpose of the study was to analyze the effect of CTPS education and practice in increasing the knowledge of Madrasah Ibtidaiyah Tarbiyatul Mubtadin students. The type of research carried out is experimental research with a pre-experimental research design one-group pretest-posttest design. The population of the study was all students of Madrasah Tarbiyatul Mubtadin with a sample of 21 students of class IV Madrasah Tarbiyatul Mubtadin. The sampling technique is total population sampling and data collection techniques are through questionnaires. Data analysis using data processing software using paired t-test. The results of the paired t-test statistic showed a value (p-value is 0.000) less 0.05 so it could be stated that there was a significant difference between the students' knowledge of handwashing with soap before and after the intervention. There was an increase in the level of students' knowledge before and after the intervention and there was an influence of education and practice on students' knowledge of Handwashing with Soap (CTPS) at Madrasah Ibtidaiyah Tarbiyatul Mubtadin during the Pandemic Period. World Health Organization sejak tanggal 11 Maret 2020 menetapkan Indonesia menjadi pandemi COVID-19. Kementerian Kesehatan dengan sigap melakukan bentuk upaya pengendalian dengan merilis Surat Edaran No.HK.02.02/I/385 supaya serentak secara aktif ikut serta dalam pencegahan penularan COVID-19 melalui gerakan Masker untuk Semua dan penyediaan sarana cuci tangan dengan sabun (CTPS). Tujuan Penelitian adalah menganalisis pengaruh edukasi dan praktik CTPS dalam peningkatan pengetahuan Siswa Madrasah Ibtidaiyah Tarbiyatul Mubtadin. Jenis penelitian yang dilakukan adalah penelitian eksperimental dengan desain penelitian pra-eksperimental one group pretest-posttest design. Populasi dari penelitian adalah seluruh siswa-siswi Madrasah Tarbiyatul Mubtadin dengan sampel yaitu siswa kelas IV Madrasah Tarbiyatul Mubtadin sebesar 21 siswa. Teknik sampling yaitu total population sampling dan teknik pengumpulan data melalui kuisioner. Analisis data menggunakan software pengolahan data menggunakan uji paired t-test. Hasil uji statistik paired t-test menunjukkan nilai (p-value sama dengan 0,000) kurang dari 0,05 sehingga dapat dinyatakan terdapat perbedaan yang signifikan antara pengetahuan Cuci Tangan Pakai Sabun siswa sebelum dan setelah intervensi. Terdapat peningkatan tingkat pengetahuan siswa sebelum dan setelah intervensi serta terdapat pengaruh edukasi dan praktik terhadap pengetahuan Cuci Tangan Pakai Sabun (CTPS) siswa di Madrasah Ibtidaiyah Tarbiyatul Mubtadin di Masa Pandemi.